Geneology of Muhammadiyah Education Movement in Indonesia: Study of Living Hadith - Rohmansyah Rohmansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Muhammadiyah education was founded in 1908, before the founding of Muhammadiyah. This education is a response to social conditions in the past such as ignorance, poverty, and underdevelopment. The response to these three things is based on religious doctrine, namely the Qur’an and hadith. This study aims to explain the hadiths that inspired Muhammadiyah to carry out educational movements as a response to social phenomena that occurred in the past and what influenced Muhammadiyah to carry out educational movements based on hadiths. The research method is a qualitative one based on observation, interviews, and library research. The findings of this study are: Muhammadiyah, through KH. Ahmad Dahlan, carried out an educational movement as a response to social problems that occurred during the Dutch colonial period. This educational movement is based on the hadiths of the Prophet, who ordered this organization to carry out reforms and renewals. Renewal in the field of education is carried out by changing the old educational model into a new one. The hadiths of the educational movement were written by two students of KH. Ahmad Dahlan, namely Sudja and KRH. Hadjid. This educational movement was influenced by four factors, namely social factors, economic factors, political factors, and cultural factors that developed in Java